(untitled) (Journal of Information Technologies in Education (ITE), 2009)
Considered are the questions of info-comunicational technology for university report information gathering and processing. It is proposed to automate the basic university reports preparation process. On the basis of the proposed system, it possible to provide electronic documents circulation between the Ministry of Education and universities of Ukraine.